Strategy Marketing Public Relations Co-Branding Compass X PMP - Muhammad Zenal; Wulan Trigartanti (UNISBA Press, 2022)
Abstract. Strategy marketing in public relations building co-branding Compass X PMP one step to develop cooperation. mutually beneficial Cooperation was aimed at just to be effective in inducing, interesting, persuade consumers to purchase products shoes limited editions Compass X PMP edition “Darahbiruku”. Strategy marketing public relations to build each other up brand image, breakthrough, and expected company stay. Company to establish cooperation through will produce innovative products, limited edision, or special products limited scale in the market. Research purposes know Compass X PMP Strategy marketing public relations in building co-branding on a series of certified limited edition “darahkubiru”. To figure out how marketing public relations co-branding on a series of certified limited edition “darahkubiru”. To know why Compass X PMP administration created marketing strategy public relations in building co-branding. Methods used a qualitative, approach a case study Robert K. Yin by design research type 1, one case , a unit of analysis. Using interviews speakers, observations, documentation, and study literature. Drawing conclusions: Compass X PMP Strategy marketing public relations co-branding on shoes series certified limited edition “darahkubiru” one of them is how to use pull strategy, push strategy, pass strategy with a view to the two companies more in, know in the eyes of consumers created attraction for consumer interest targets and new consumer, and build respect, value , credibility when cooperation Compass X PMP so as to create a good reputation and appreciative. Abstrak. Strategi marketing public relations dalam membangun co-branding Compass X PMP salah satu langkah membangun mitra saling menguntungkan. Kerjasama itu bertujuan supaya lebih efektif dalam mendorong, menarik, membujuk konsumen untuk membeli produk sepatu limited editions Compass X PMP edisi “Darahbiruku”. Strategi marketing public relations bertujuan saling membangun brand image, sehingga dengan terobosan co-branding, diharapkan perusahaan tetap bertahan. Perusahaan yang berani membangun kerjasama melalui co-branding akan menghasilkan produk yang inovatif, limited editions, ataupun produk khusus berskala terbatas di pasaran. Tujuan penelitian mengetahui Compass X PMP menciptakan strategi marketing public relations dalam membangun co-branding pada sepatu seri bersertifikat limited edition “Darahkubiru”. Untuk mengetahui cara marketing public relations co-branding pada sepatu seri bersertifikat limited edition “Darahkubiru”. Untuk mengetahui mengapa Compass X PMP menciptakan strategi marketing public relations dalam membangun co-branding. Metode yang digunakan yaitu kualitatif, pendekatan studi kasus Robert K. Yin dengan desain penelitian tipe 1, satu kasus, satu unit analisis. Menggunakan wawancara narasumber, observasi, dokumentasi, dan studi kepustakaan. Simpulan: Compass X PMP menciptakan strategi marketing public relations dalam membangun co-branding pada sepatu seri bersertifikat limited edition “Darahkubiru” salah satunya dengan cara menggunakan pull strategy, push strategy, pass strategy dengan tujuan agar kedua perusahaan lebih di kenal di mata konsumen, menciptakan daya tarik bagi minat konsumen target dan konsumen baru, serta membangun nilai respect, kredibilitas, pada saat kerjasama Compass X PMP sehingga menciptakan reputasi yang baik serta apresiatif.